Computer Based Sequential and Simultaneous Dual‐Task Training for Executive Functions in Elderly: A 2‐Arm Protocol for a Randomized Controlled Study. - Samnani, Anjum; Azharuddin, Muhammad; Parveen, Sarah; Noohu, Majumi M.; Sehgal, Chhavi Arora (Physiotherapy Research International, 2026)
Background: Normal aging corresponds to neuroanatomical changes such as gray and white matter atrophy, particularly in the prefrontal cortex. These can lead to a decline in cognitive skills such as executive functions, processing speed, and working memory that leads to eventual challenges in performing activities of daily living and limits independent life. Dual‐task training is known to be effective in these functions, but the evidence on the comparison between sequential and simultaneous dual‐task training remains inconclusive. Objectives: The main objectives of this randomized controlled trial (RCT) are to compare the effectiveness of sequential (SEQ‐DTT) and simultaneous dual‐task training (SIM‐DTT) on executive functions and balance (static and dynamic) in older adults that combines balance training and computerized cognitive training. Method: Forty‐six older adults (60 years old or above) will be randomly allocated to one of the two groups: SEQ‐DTT or SIM‐DTT to carry out 60 min of balance training and cognitive intervention either sequentially or simultaneously, respectively, 3 times a week for 8 weeks. We will assess Event‐related potential P300 (ERP P300), Trail Making Test (TMT), Stroop Colour and Word Test (SCWT), One Leg Standing Test (OLST), Timed Up and Go Test (TUG), 10 Meter Walk Test (10MWT) & 10 Meter Walk Test—Dual‐Task (10MWT‐DT). The comparison within the groups and between the groups at baseline and after 8 weeks of intervention will be done using independent t‐test and one‐way ANOVA, respectively. Conclusion: The study will help understand the effectiveness of computer‐based training in the elderly population for executive functions and the changes in the balance. Trial Registration: The study was registered in the Clinical Trial Registry‐India (CTRI) with reference number CTRI/2023/12/060793 on 27/12/2023